2018
DOI: 10.1097/meg.0000000000001087
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prognostic performance of Albumin–Bilirubin, Child–Pugh, and Model for End-stage Liver Disease scores in patients with liver cirrhosis complicated with acute upper gastrointestinal bleeding

Abstract: In our series, the ALBI score accurately predicted both in-stay and 30-day mortality, whereas CP and MELD scores could not predict these outcomes. All scores showed a fair prognostic prediction performance for first-year and global mortality. These results suggest that the ALBI score is particularly useful in the assessment of short-term outcomes, with a better performance than the most commonly used scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
18
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
9
18
1
5
Order By: Relevance
“…Decompensated cirrhosis is a common disease with high morbidity and may be accompanied by several manifestations of decompensation, including gastrointestinal hemorrhage, hepatic encephalopathy, and infection. Consistent with a previous study on patients with liver cirrhosis, approximately 11.0% of patients with decompensated cirrhosis died within 28 days and 20% died within 6 months in the present study [26][27][28]. To reduce mortality, it is crucial to recognize those patients with a potentially poor prognosis and then prioritize and treat them accordingly in an appropriate and timely manner.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Decompensated cirrhosis is a common disease with high morbidity and may be accompanied by several manifestations of decompensation, including gastrointestinal hemorrhage, hepatic encephalopathy, and infection. Consistent with a previous study on patients with liver cirrhosis, approximately 11.0% of patients with decompensated cirrhosis died within 28 days and 20% died within 6 months in the present study [26][27][28]. To reduce mortality, it is crucial to recognize those patients with a potentially poor prognosis and then prioritize and treat them accordingly in an appropriate and timely manner.…”
Section: Discussionsupporting
confidence: 87%
“…Lei et al's study shows that ALBI scores are consistent with the Child-Pugh score and the MELD scores in predicting value of patients with hepatitis B-related liver disease [14]. Similar to the conclusion of Xavier et al's study, we found that the ALBI score has a better performance than the Child-Pugh score and the MELD scores in predicting short-term prognosis, especially in patients with acute decompensation of cirrhosis [28]. Xavier et al's study mainly focused on patients with cirrhosis complicated by acute upper gastrointestinal bleeding, which is similar to the cause of hospitalization in this study.…”
Section: Disease Markerssupporting
confidence: 88%
“…Positive correlations was also found between the ALBI score and the CTP score (r= +0.576, p< 0.001) [26]. Strong positive correlation between the ALBI and the CTP score (r = 0.759, p< 0.01) was evident [20]. These results are consistent with the current study.…”
Section: Discussionsupporting
confidence: 91%
“…This result is not consistent with the present study. In a study observed among 111 cirrhotic patients during assessing prognostic performance of ALBI score in Portugal among other scores, the mean± SD of serum albumin (g/dl), serum bilirubin (mg/dl), prothrombin time (sec) and INR were 2.6±0.6, 2.5±2.4, 17.5±3.9, 1.6±0.4 respectively [20]. These findings are nearly similar with our study.…”
Section: Discussionsupporting
confidence: 91%
“…27 Although ALBI score was introduced to assess the liver function in patients with HCC, 28 yet different recent studies proved its usefulness in predicting complication and survival for patients with liver cirrhosis when complicated with acute liver failure, 29 or acute UGIB. 30 More recently, its use in the assessment of patients undergoing living donor transplantation was studied. 31 ALBI score, compared with the traditional MELD and CP scores, is more simple, easy, and readily comparable.…”
Section: Discussionmentioning
confidence: 99%